Parametric design as an approach for design for additive manufacturing - Djokikj Jelena, Kanidkjan Tatjana (Serbian Society for Geometry and Graphics, 2020)
Additive Manufacturing (AM) refers to a group of processes that experienced rapid development over the last decade. This enabled their applicability in various areas. Their specific manner of functioning through adding material is the reason why they are so versatile. Still, at the same time, this specific manner of functioning demands a different approach in the design process, the so-called design for additive manufacturing (DfAM). DfAM is an approach based on the principle of the well-known DFM (Design for Manufacturing) and DFMA (Design for Manufacturing and Assembly). The aim of the DfAM is to help designers to adapt more easily to AM and fully exploit its possibilities. One of the most important AM advantages is the fabrication of complex geometries, which is particularly interesting to designers. Regardless of all the advantages, there are some restrictions to the AM processes that need to be taken into consideration in the design process. In this paper, we propose the use of parametric design for designing unique models with complex geometries. Through designing the parameters, we can implement the AM restrictions in the early stages of the design process without affecting the complexity of the shape. Another advantage of the parametric design is the possibility of easy manipulation of the CAD model and a change of the parameters, so that a whole collection of unique products can be created.
Keywords: Design for additive manufacturing (DfAM); parametric design; design process